The Influence of Female Leadership Style on Communication Climate and Job Satisfaction - Fitri, Rachmawati Aulia; Putri, Idola Perdini (Gulawentah:Jurnal Studi Sosial, 2023)
This research aims to find out how female leadership style affects the communication climate and job satisfaction at PT. Indonesian Digital Identity. Using the total sampling method, a total sample of 100 respondents was gathered from Sati Rasuanto's staff. The method used to analyze the data is path analysis. According to calculations performed with the SmartPLS software version 3.0, the results show a significant relationship between the influence of female leadership style on the communication climate, The communication atmosphere at work has a much greater impact on employee happiness than does the female leadership style. The implications of the results of the study indicate that leaders need to increase democratic and participatory traits such as tolerance, empathy, and openness to the perspectives and ideas of others in women's leadership so that the climate of communication and job satisfaction can be adequately maintained.